Manfaat Irigasi Springkler pada Lahan Fasum untuk Peningkatan Produksi Pertanian Kampung Tangguh Poharin - Mundra, I Wayan; Wulandari, Lies Kurniawati; Sebayang, Nusa (STIE Malangkucecwara, 2023)
This community service is the result of research in 2022 which will be poured on community service on the fasum land in Pondok Harapan Indah housing, Jalan Sigura-Gura Malang. Installation of pipes and sprinkler nozzles based on distance and height according to the type of plant that exists. With the potential for water sources and limited land area, farmers' businesses are expected to be able to utilize water efficiently. The sprinkler irrigation system is thought to be an alternative in the provision of irrigation and for this reason it is necessary to test the ability of the irrigation system to vary the distance between the sprinklers and the high sticks to the irrigation radius and its uniformity within a few minutes duration. For a stick height of 1 m with the same sprinkler spacing, a uniformity coefficient of less than 80% is obtained and the optimal irrigation radius is with an average spacing of 6 meters